Dark waters ebook - Arden, Katherine (Small Spaces Quartet, 2021)
An Indie Bestseller! Filled with chills, New York Times bestselling author Katherine Arden’s latest installment in the creep-tastic Small Spaces Quartet is sure to haunt. Until next time. That was chilling promise made to Ollie, Coco and Brian after they outsmarted the smiling man at Mount Hemlock Resort. And as the trio knows, the smiling man always keeps his promises. So when the lights flicker on and off at Brian's family's inn and a boom sounds at the door, there's just one visitor it could be. Only, there's no one there, just a cryptic note left outside signed simply as —S. The smiling man loves his games and it seems a new one is afoot. But first, the three friends will have to survive a group trip to Lake Champlain where it's said Vermont's very own Loch Ness monster lives. When they’re left shipwrecked on an island haunted by a monster on both land and sea, Brian's survival instincts kick in and it's up to him to help everyone work together and find a way to escape. One thing is for sure, the smiling man is back and he wants a rematch. And this time Brian is ready to play.